2021
DOI: 10.1038/s41392-020-00445-8
|View full text |Cite
|
Sign up to set email alerts
|

The double face of miR-320: cardiomyocytes-derived miR-320 deteriorated while fibroblasts-derived miR-320 protected against heart failure induced by transverse aortic constriction

Abstract: MicroRNAs (miRNAs) are aberrantly expressed in the pathophysiologic process of heart failure (HF). However, the functions of a certain miRNA in different cardiac cell types during HF are scarcely reported, which might be covered by the globe effects of it on the heart. In the current study, Langendorff system was applied to isolate cardiomyocytes (CMs) and cardiac fibroblasts (CFs) from transverse aortic constriction (TAC)-induced mice. Slight increase of miR-320 expression was observed in the whole heart tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…A similar finding was also reported in our previous study. MiR-320 levels were significantly elevated in cardiomyocytes but were decreased in cardiac fibroblasts, thereby leading to a slight increase in miR-320 expression in the global heart tissue of TAC mice ( Zhang et al., 2021 ). Moreover, another study showed a decreased expression trend in SARS-CoV-2-infected human induced pluripotent stem cell (iPSC)-derived cardiomyocytes, as detected by RNA-seq ( Sharma et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A similar finding was also reported in our previous study. MiR-320 levels were significantly elevated in cardiomyocytes but were decreased in cardiac fibroblasts, thereby leading to a slight increase in miR-320 expression in the global heart tissue of TAC mice ( Zhang et al., 2021 ). Moreover, another study showed a decreased expression trend in SARS-CoV-2-infected human induced pluripotent stem cell (iPSC)-derived cardiomyocytes, as detected by RNA-seq ( Sharma et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…As an example, sdRNA-93 and sno-miR-28 regulate cell proliferation by repressing the p53-stabilizing transcription initiation factor TFIID subunit 9b (TAF9B) [ 88 , 89 , 90 ]. MiR-320 is dysregulated in ischemic hearts, where its inhibition using anti-miR-320 reduces cardiac infarction size [ 91 ]. Moreover, it is highly expressed in the pancreatic islets of Langerhans, where it suppresses insulin resistance.…”
Section: Non-canonical Function Of Ncrnas In Cvdmentioning
confidence: 99%
“…Upon hyperglycemia, cardiomyocyte-derived exosomes are enriched in miR-320 which inhibits endothelial cell proliferation and perpetuates cell dysfunction in the onset of diabetes-associated cardiomyopathy [142]. Cardiac remodeling and fibrosis can also be associated to exosomal non-coding RNAs in cardiomyopathy.…”
Section: Cardiomyopathymentioning
confidence: 99%